Analyse der Realnutzung von Elektrofahrzeugen in kommerziellen Flotten zur Definition einer bedarfsgerechten Fahrzeugauslegung - Pfriem, Matthias (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2016)
Based on a naturalistic driving study with electric vehicles in commercial fleets, a detailed analysis of mobility is conducted to derive an empirically founded tailor-made vehicle specification, which focuses on the core of the user demand and excludes statistical outliers in favour of a more economical design. Furthermore, real-world driving cycles for electric vehicles are created and the market potential of such a tailor-made vehicle is estimated.